Evolving social capital and networks in the post‐disaster rebuilding process: The case of Typhoon Yolanda. (2nd March 2020) - Tan‐Mullins, May; Eadie, Pauline; Atienza, Maria Ela
Abstract : Typhoon Yolanda brought major devastation to the local communities and infrastructure and also reshaped social structures and networks in the Philippines. During the immediate recovery process, bridging, bonding and linking social capital have had differential impacts and outcomes on how communities cope with the aftermath of the disaster. This article investigates the interplay between the various types of social capital and their contributions to immediate coping strategies of Typhoon Yolanda communities. This article also evaluates the complexity of defining social capital in a disaster context. In particular, it unpacks the blurring of the bridging and linking social capital at the immediate stage of rehabilitation in a post‐disaster context and its impacts on the social fabric of the communities. We deduce from this case study the social capital strategies necessary for a speedy recovery process both economically and socially for disaster‐affected communities.